PENGEMBANGAN MEDIA E-LEARNING BERBASIS LMS MOODLE PADA MATAKULIAH ANATOMI FISIOLOGI MANUSIA - Azis, Andi Asmawati (Universitas Negeri Malang, 2015)
The limit of face to face learning presented the recent alternative solution in technology named E-learning. This Research and Development (R and D) aims to produce media-based e-learning LMS Moodle, in the course of Human Anatomy Physiology. The research was conducted in Class Human Anatomy Physiology, Biology Education Study Program V Semester 2014 Faculty UNM. The data were collected by using questionnaire to measure validity, practical, and effectiveness. The R and D’s model used Analyze, Design, Develop, Implement, Evaluate (ADDIE) comprised of initial data collecting, design of research instrument and Moodle, development of research instrument and Moodle, trial and error to subjects, and evaluation .The result of this study noted that media-based e-learning LMS Moodle is very useful in improving the quality of lecture courses of human anatomy and physiology. This increase can be seen from the use of e-learning facilities by students in the course of Human Anatomy Physiology, increased activity of learning, and students attitude towards human physiology and anatomy course.